2000
DOI: 10.1109/23.903824
|View full text |Cite
|
Sign up to set email alerts
|

Single event effects in circuit-hardened SiGe HBT logic at gigabit per second data rates

Abstract: This attempt at circuit level single event effects (SEE) hardening of SiGe HBT logic provides the first reported indication of the level of sensitivity in this important technology. Characterization over data rate up to 3 Gbps and over a broad range of heavy ion LET's provides important clues to upset mechanisms and implications for upset rate predictions. We augment ion test data with pulsed laser SEE testing to indicate the sensitive targets within the circuit and to provide insights into the upset mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 22 publications
4
50
1
Order By: Relevance
“…Circuit A is the unhardened version of the D flip-flop used in the shift registers tested in [2]. The transistor level circuit is shown in Fig.…”
Section: A Circuit a B And Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Circuit A is the unhardened version of the D flip-flop used in the shift registers tested in [2]. The transistor level circuit is shown in Fig.…”
Section: A Circuit a B And Dmentioning
confidence: 99%
“…SEU sensitivity in SiGe HBT digital logic, as it is for any bipolar logic, depends on the circuit implementation, and hence one can in principle alter the circuit configuration in order to minimize SEU sensitivity. Previously, a comparison of SEU response in multiple SiGe HBT digital logic circuits indicated that cross-coupling at the transistor level in the storage cell negates any moderate SEU immunity achieved through circuit-level hardening using the current-shared hardening (CSH) [1] technique [2]. In this work, we propose an implementation of D flip-flop digital logic with a new circuit architecture featuring limited transistor-level decoupling in the storage cell and compare its predicted SEU response with three other circuit architectures.…”
mentioning
confidence: 99%
“…The angles used for simulation correspond to the angles used in broadbeam testing [13][14][15]. The "Effective LET" from Fig.…”
Section: Ion Strike Simulation Methodologymentioning
confidence: 99%
“…• A patterned subcollector (n for npn, p for pnp) on a doped substrate SiGe HBTs have been found to be quite tolerant to total ionizing dose (the amount of trapped charge accumulated over time found typically in the oxides and oxide interfaces of the device) and displacement effects (the result of lattice defects typically attributed to non-ionizing nuclear scattering reactions) [5][6][7][8][9][10][11], but are vulnerable to SEU [12][13][14][15][16]. [16].…”
Section: Event Effect (See)mentioning
confidence: 99%
See 1 more Smart Citation